The Application Of Flip Book Media to Increasing Elementary Children's Learning Interest - Lakapu, Pifa A.; Djara, Jean I.; Lakapu, Dyen E.; Nifus, Debrina A. (International Journal of Educational Sciences and Development, 2023)
The purpose of the research is to increase the interest of studying the boys in the co-educacy, rt/ rw 003 / 006.The method used is a method of study of class action.The research subject is a school age boy.Using extra flipbooks compared to other media, which is that the presentation of matter is much more interesting because it can combine text, Audio, The video, image, Even the animated flash of the finality of learning children exposed on the i cycle is that children reach complete or get only 70 are just 15 (65 %) children of 20 children.Classically completed children are only 85 %s, while to meet effective completion has to reach 85 %s, So it can be said that on the i cycle the results of children's learning are said to be classicly incomplete.On the ii cycle it was obtained that the results of children's learning were 19 (95 %) children from 20 children.Means children's learning results have reached 95 %. So it can be concluded that in the cycle II, children's regularity to learn using flipbook learning media to improve children's learning outcomes on climate change material in the degradation of kobekamusa, rt / rw 003 / 006, The city of warm, Increased compared to the number of cycles I.